Increased LDH5/LDH1 ratio in preoperative diagnosis of uterine sarcoma with inconclusive MRI and LDH total activity but suggestive CT scan: a case report - Antonio Mollo; Antonio Raffone; Antonio Travaglino; Annalisa Di Cello; Gabriele Saccone; Fulvio Zullo; Giuseppe De Placido (BMC, 2018)
Abstract Background Morcellation of undiagnosed uterine sarcoma is cause of abdominal/pelvic dissemination, residual tumor and recurrence. In the preoperative evaluation of suspect uterine masses, magnetic resonance imaging (MRI) and serum lactate dehydrogenase (LDH) total activity are referred to as the most effective tools, while computed tomography scan (CT) and LDH isoenzymes are less considered in literature. Case presentation A 46 year old woman was admitted to our department with a large uterine mass. Ultrasonography, MRI and LDH total activity did not allow a diagnosis of malignancy, and the woman expressed the wish to avoid hysterectomy. In spite of this, we opted for a total abdominal hysterectomy instead of a laparoscopic myomectomy, due to an elevation of LDH5/LDH1 ratio and CT findings indicative of sarcoma. Histological examination revealed a high grade leiomyosarcoma, confirming our suspicion. Thus, we had avoided the risks linked to morcellation. Conclusions Our experience suggests that LDH isoenzymes assessment may be relevant in preoperative diagnosis of uterine sarcoma. Further studies are necessary to determine its role in a diagnostic algorithm. We think it may be useful especially for patients with clinical or ultrasonographic suspicion of uterine sarcoma not confirmed by imaging techniques. Furthermore, the role of less considered imaging techniques, such as CT, should not be underestimated in challenging cases.